DETERMINATION OF THE FUEL CONSUMPTION OF A CAR IN THE CYCLE OF MOVEMENT IN URBAN CONDITIONS (IN THE MATLAB PROGRAM) - Ismadiyorov Asrorjon Anvarjon o‘g‘li (Web of Journals Publishing, 2023)
In this article, the determination of the influence of the parameters of the driving conditions of the car on its fuel consumption, the reasonable selection of the parameters of the car for certain operating conditions, and the research of determining the norm of the fuel consumption of the car in the given conditions require long-term test research. The current state of information technology and several computer software provides an opportunity to evaluate the existing processes employing simulation modelling.
Keywords: drive cycle, car, fuel consumption, moderation, economy, resource.